2019
DOI: 10.1097/nne.0000000000000711
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Dedicated Education Unit Model for ADN Students in a Rural Primary Care Setting

Abstract: Background Dedicated education unit (DEU) clinical education models are an innovative, evidence-based approach to create effective learning environments for students. These models have been implemented primarily in acute care settings. Problem The gap between nursing education and clinical practice in rural health care settings is a growing concern, compounded by a nursing faculty shortage and decreased availability of clinical sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The outcomes of the studies included in this review were grouped into seven main categories, namely relationships, influence, the environment, facilitation, inputs, knowledge scores, and student perceptions. Firstly, relationships were reported as outcomes of specific models, such as belonging to a team [ 55 ], peer support among students [ 26 ], and helpful or positive relationships [ 40 ]. Nordquist et al , [ 64 ] explain the importance of positive relationships where students learn from and with their peers and facilitators.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the studies included in this review were grouped into seven main categories, namely relationships, influence, the environment, facilitation, inputs, knowledge scores, and student perceptions. Firstly, relationships were reported as outcomes of specific models, such as belonging to a team [ 55 ], peer support among students [ 26 ], and helpful or positive relationships [ 40 ]. Nordquist et al , [ 64 ] explain the importance of positive relationships where students learn from and with their peers and facilitators.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the studies included in this review were grouped into seven main categories, namely relationships, in uence, the environment, facilitation, inputs, knowledge scores, and student perceptions. Firstly, relationships were reported as outcomes of speci c models, such as belonging to a team [55], peer support among students [26], and helpful or positive relationships [40]. Nordquist et al, (2019) [64] explain the importance of positive relationships where students learn from and with their peers and facilitators.…”
Section: Discussionmentioning
confidence: 99%
“…20 Several studies have investigated the effectiveness of the DEU model in promoting collaborative interprofessional teamwork among nursing students. 7,14,17,[21][22][23][24][25][26][27][28] Most of these studies were qualitative (n = 8) and reported teamwork and collaboration by students as a major recurring theme. 7,14,17,21,22,[24][25][26] Students who participated in the DEU felt accepted by clinicians on the unit, which in return assisted students in more actively engaging in their clinical work.…”
Section: Teamwork and Collaborationmentioning
confidence: 99%
“…7,14,17,[21][22][23][24][25][26][27][28] Most of these studies were qualitative (n = 8) and reported teamwork and collaboration by students as a major recurring theme. 7,14,17,21,22,[24][25][26] Students who participated in the DEU felt accepted by clinicians on the unit, which in return assisted students in more actively engaging in their clinical work. 21,22,[24][25][26] Students also reported that they were welcomed and supported by health care teams.…”
Section: Teamwork and Collaborationmentioning
confidence: 99%